A HYBRID APPROACH FOR OPTIMAL AND COMPACT DESIGN OF A COST-EFFECTIVE MAGNETIC ACTUATOR FOR INDUSTRIAL APPLICATIONS - Selzam, Jan Harald; Binner, Pascal; Meier, Trixi; Hanenkamp, Nico (MM Science Journal, 2025)
Carbon dioxide (CO2) based cryogenic minimum quantity lubrication (cMQL) is an alternative approach to facilitate cooling lubrication of cutting processes. While it offers greater sustainability than conventional metalworking fluids (MWF), its precise, process-specific dosing can be challenging. This is due to the physical properties of the pressurized CO2, as it already develops its cooling effect in the supply line if expanding there. The paper therefore proposes a new approach to the dosing of this coolant strategy which is based on high-frequency pulsed application. By opening and closing a valve in the immediate vicinity of the application nozzle at high frequency, a precisely adjustable fraction of the maximum mass flow can be directed to the cutting zone. This allows the cooling capacity to be adjusted accurately and adapted to the process. In addition, the proposed setup makes it possible to react to the fluctuating input quality of the CO2. This paper examines how accurately the mass flow can be dosed using high-frequency CO2 pulses. It also investigates whether continuous and pulsed cMQL have comparable cooling capacities at the same mass flow rate and to what extend the input quality of the CO2 can be compensate
Keywords: Cryogenic cooling; pulsed coolant application; adaptive dosing